AberGlide Backpack Enterprise / Wan Nur Amira Balqis Wan Razali - Wan Razali, Wan Nur Amira Balqis (2020)
AberGlide Backpack Enterprise is a partnership company that has been established on 18th March 2019. AberGlide is high quality products that innovation from the existing backpack to the high-technology use as combination of suspension system or pulley system with automatic-timer massager system. AberGlide came with four designs and four sizes. Each design have their specific name and characteristics to distinguish with existing design and brand. These innovation backpack suitable for teenagers , hikers, travellers or active people.AberGlide is the leading modern and innovative backpack, relieve stress and strain